Readiness for interprofessional learning among dental undergraduate students: An institutional study - S Sibyl; Darshana Bennadi; Nandita Kshetrimayum; C.V.K. Reddy (Wolters Kluwer Medknow Publications, 2018)
Introduction: In today's health-care services, there is no clear-cut role of each profession. These roles have been shaded or blended with the roles of each other professions, which shows an interconnection between each profession. Interprofessional learning is an approach of learning with each other's professional knowledge and skills. This type of learning will be helpful for the students to enhance their knowledge, skills, interaction, and provision of health-care services. Aim: The objective of this study was to assess the attitude of dental undergraduate students toward interprofessional learning. Materials and Methods: This descriptive questionnaire study was conducted on dental undergraduate students in Mysore city. A total of 250 dental students were selected using stratified random sampling method. Data were collected using a questionnaire on Readiness for Interprofessional Learning Scale. Results: Among the 250 dental undergraduate students who completed the survey, 27.6% (n = 69) were males and 72.4% (n = 181) were females. Nearly 84% (n = 210) showed positive attitude toward team work and collaboration as a result of shared learning and 16% (n = 40) had negative attitude. When asked about their view toward professional identity, 85.6% (n = 214) felt that interprofessional learning will help them understand their professional identity better and 15.4% (n = 36) disagreed it. Conclusion: Dental undergraduate students in general have a positive view toward interprofessional learning.